Identifying and Prioritizing the Effective Criteria in Selecting Lean Six Sigma Improvement Projects in the Healthcare Sector - Ardeshir Bazrkar; Vahid Aramoon; Erfan Aramoon (WPOM : Working Papers on Operations Management)
The main objective of this study was to identify and prioritize effective criteria in selecting Lean Six Sigma improvement projects in the healthcare and treatment sector in Iran. The present study was an applied research in terms of objective and a descriptive and analytical one according to the research methodology and data collection approach. The research statistical population included experts and managers with experience in the field of implementing the lean six sigma methodology in the field of healthcare and treatment in Iran. We used interviews and questionnaire tools to collect the data. The effective criteria were identified through reviewing previous research, which were then prioritized based on the experts’ opinions using the BWM method. According to the results, out of the six main dimensions and 20 criteria identified, the customer development dimension with a weight of 0.387 and the customer satisfaction criterion with a weight of 0.066 were determined as the most effective dimension and the most effective criterion, respectively. Accordingly, the directors of medical centers and organizations affiliated with the healthcare sector are recommended to pay special attention to these defined criteria of the customer development dimension to effectively implement the lean six sigma methodology and managing an effective customer relationship.